2004
DOI: 10.3354/meps268081
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of water flow inside seagrass canopies of differing structure

Abstract: An understanding of how habitat structure influences physical environmental processes that are important to organisms utilizing the habitat is a necessary basis for predicting biological responses to habitat variation. Seagrass meadows represent an important coastal nursery habitat that modifies the local flow environment. We used basic fluid-dynamic balances to construct a simple model of the effects of seagrass habitat structure on mean flow within and above the canopy, and tested quantitative predictions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
2
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 42 publications
3
105
2
8
Order By: Relevance
“…Previous work has shown that the depth-averaged form of Eq. 1 correctly predicts the depth-averaged velocity within an emergent canopy (Peterson et al 2004); we consider the vertical variation in vegetation density in order to resolve the vertical structure in the velocity profile. Because ‫‪x‬ץ/ץ‬ is not a function of vertical position in the water column, the quantity C d au 2 is constant over depth.…”
Section: Analytic Developmentmentioning
confidence: 99%
“…Previous work has shown that the depth-averaged form of Eq. 1 correctly predicts the depth-averaged velocity within an emergent canopy (Peterson et al 2004); we consider the vertical variation in vegetation density in order to resolve the vertical structure in the velocity profile. Because ‫‪x‬ץ/ץ‬ is not a function of vertical position in the water column, the quantity C d au 2 is constant over depth.…”
Section: Analytic Developmentmentioning
confidence: 99%
“…Granata et al (2001) showed that hydrodynamics may be reduced both under and above the canopies by 10 to 75%. In summary, higher flow attenuation has been observed inside canopies with increasing shoot density (Leonard & Luther 1995, Koch & Gust 1999, Peterson et al 2004, Nepf et al 2007, Hansen & Reidenbach 2012, Pujol et al 2012, 2013a,b) Pujol et al (2013b conducted oscillatory flow experiments in the laboratory using a submerged flexible canopy constructed to simulate P. oceanica properties. They found orbital velocity reductions of 22 and 39% for solid plant fractions (SPF; i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Seagrass canopies are known to reduce flow and turbulence (Fonseca et al 1982, Gambi et al 1990, Ackerman & Okubo 1993, Koch 1996, Gacia et al 1999, Koch & Gust 1999, Nepf & Vivoni 2000, Jumars et al 2001, Peterson et al 2004, Koch et al 2006) and attenuate wave action (Fonseca & Cahalan 1992, Koch & Gust 1999, Granata et al 2001, Bouma et al 2005, Koch et al 2006, thereby promoting sedimentation and reducing resuspension within seagrass meadows (Gacia et al 1999, Terrados & Duarte 2000. Examination of the composition of the material deposited within seagrass canopies has revealed the presence of a large (> 50%) contribution of sestonic particles (Gacia et al 2002), pointing to a large pelagic particle flux toward seagrass meadows.…”
Section: Introductionmentioning
confidence: 99%